VD_FINDINFO Jug / 2024 / 206 vom 15. Juli 2024 - VD Tribunal cantonal (2024)
DÉBAUCHAGE, CONCURRENCE DÉLOYALE | 3 al. 1 let. b LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 4 let. a LCD, 5 LCD, 222 al. 2 CPC (CH), 223 al. 1 CPC (CH), 223 al. 2 CPC (CH)